Deep X-ray lithography on "sol–gel" processed noble metal mesoarchitectured films. Issue 5 (19th January 2022) - Gayrard, Maxime; Marmiroli, Benedetta; Chancerel, Francois; Decorse, Philippe; Amenitsch, Heinz; Peron, Jennifer; Cattoni, Andrea; Faustini, Marco
Abstract : Noble metal coordination xerogel exhibit solubility switch when exposed to X-rays. The films can be used as recyclable negative tone resists for deep X-ray lithography that can be converted into metallic nanoarchitectured films. Abstract : Noble metal coordination xerogel films (mesostructured with block-copolymers) exhibit solubility switching with increasing X-ray irradiation. Different from other sol–gel systems, these are attributed to film deconstruction under irradiation. These materials can be used as recyclable negative tone resists for deep X-ray lithography that can be further converted into metallic nanoarchitectured films.